Intestinal Barrier Function and the Gut Microbiome Are Differentially Affected in Mice Fed a Western-Style Diet or Drinking Water Supplemented with Fructose. Issue 5 (29th March 2017) - Volynets, Valentina; Louis, Sandrine; Pretz, Dominik; Lang, Lisa; Ostaff, Maureen J; Wehkamp, Jan; Bischoff, Stephan C
Abstract: Background: The consumption of a Western-style diet (WSD) and high fructose intake are risk factors for metabolic diseases. The underlying mechanisms are largely unclear. Objective: To unravel the mechanisms by which a WSD and fructose promote metabolic disease, we investigated their effects on the gut microbiome and barrier function. Methods: Adult female C57BL/6J mice were fed a sugar- and fat-rich WSD or control diet (CD) for 12 wk and given access to tap water or fructose-supplemented water. The microbiota was analyzed with the use of 16S rRNA gene sequencing. Barrier function was studied with the use of permeability tests, and endotoxin, mucus thickness, and gene expressions were measured. Results: The WSD increased body weight gain but not endotoxin translocation compared with the CD. In contrast, high fructose intake increased endotoxin translocation 2.6- and 3.8-fold in the groups fed the CD + fructose and WSD + fructose, respectively, compared with the CD group. The WSD + fructose treatment also induced a loss of mucus thickness in the colon (−46%) and reduced defensin expression in the ileum and colon. The lactulose:mannitol ratio in the WSD + fructose mice was 1.8-fold higher than in the CD mice. Microbiota analysis revealed that fructose, but not the WSD, increased the Firmicutes:Bacteroidetes ratio by 88% for CD + fructose and 63% for WSD + fructose compared with the CD group. Bifidobacterium abundance was greater in the WSD mice than in the CD mice (63-fold) and in the WSD + fructose mice than in the CD + fructose mice (330-fold). Conclusions: The consumption of a WSD or high fructose intake differentially affects gut permeability and the microbiome. Whether these differences are related to the distinct clinical outcomes, whereby the WSD primarily promotes weight gain and high fructose intake causes barrier dysfunction, needs to be investigated in future studies.